2010
DOI: 10.1055/s-0030-1248088
|View full text |Cite
|
Sign up to set email alerts
|

Zolpidem Reduces Postoperative Pain, Fatigue, and Narcotic Consumption Following Knee Arthroscopy: A Prospective Randomized Placebo-Controlled Double-Blinded Study

Abstract: Sixty-eight patients undergoing outpatient knee arthroscopy for treatment of meniscal tears or loose bodies were divided into three treatment groups (zolpidem [24 patients], control [24 patients], and placebo [20 patients]). All groups received postoperative hydrocodone and ibuprofen. Patients in the zolpidem group received a single dose of zolpidem tartrate for the fi rst seven postoperative nights. Patients in the placebo group received a gelatin capsule similar in appearance to zolpidem and patients in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…Conversely, successful treatment of insomnia may improve certain comorbidities such as depression 48 and surgery-related pain. 49 Physicians also should be alert to the possibility of new-onset insomnia in chronically ill patients, as a fair proportion develop sleep problems. 44 Evaluating the Patient A problem-focused physical examination and detailed medical history of the patient, as well as a history of the sleep complaint, can help establish the proper diagnosis.…”
Section: Other Sleep Disorders and Insomniamentioning
confidence: 99%
“…Conversely, successful treatment of insomnia may improve certain comorbidities such as depression 48 and surgery-related pain. 49 Physicians also should be alert to the possibility of new-onset insomnia in chronically ill patients, as a fair proportion develop sleep problems. 44 Evaluating the Patient A problem-focused physical examination and detailed medical history of the patient, as well as a history of the sleep complaint, can help establish the proper diagnosis.…”
Section: Other Sleep Disorders and Insomniamentioning
confidence: 99%
“…2,3 There was also a significant reduction in narcotic usage in patients given zolpidem compared with the control group, but again not with the placebo group. 2,3 Zolpidem may have either an agonist or antagonist effect on algesia and its inflammatory mediators, such as histamine, prostaglandins, or cytokines. 4 Zolpidem has been shown to decrease total lipids, total cholesterol, and triglycerides in hyperlipidemia induced by administration of a non-ionic detergent (Triton WR-1339).…”
Section: O B S E R V At I O N Discussionmentioning
confidence: 90%
“…2,3 Both studies found that there was a significant improvement in pain and fatigue in patients given zolpidem compared with the control group, but not with the placebo group. 2,3 There was also a significant reduction in narcotic usage in patients given zolpidem compared with the control group, but again not with the placebo group. 2,3 Zolpidem may have either an agonist or antagonist effect on algesia and its inflammatory mediators, such as histamine, prostaglandins, or cytokines.…”
Section: O B S E R V At I O N Discussionmentioning
confidence: 99%
“…The analgesic efficacy of the imidazopyridine hypnotic agent zolpidem was compared with placebo and control following knee arthroscopy [53]. Pain intensity, rescue medication consumption, and fatigue were significantly reduced in the zolpidem group compared with control.…”
Section: Resultsmentioning
confidence: 99%